The views of children and young people on the use of silk garments for the treatment of eczema: a nested qualitative study within the CLOTHing for the relief of Eczema Symptoms (CLOTHES) randomized controlled trial. (1st January 2018) - Wake, E.V.; Batchelor, J.; Lawton, S.; Thomas, K.S.; Harrison, E.F.; Cowdell, F.C.
Summary: This study reports on a trial from the U.K. to find out if specialised silk clothing improved eczema in children. Eczema is a common skin condition. It affects around one in five children and can cause sore and itchy skin, poor sleep and reduced quality of life. As part of this work the researchers wanted to find out what the children who wore the garments in the study thought of them. They invited 18 children aged between five and 15 years to take part, meeting in small groups and using stories and play to help the children tell the researchers about the garments. All the children and young people had high hopes that the garments would make their skin much better. They expected the garments to feel soft and smooth and were disappointed when they were not like this. They reported that they mostly wore them at night as it was embarrassing to wear them during the day. Some said that the garments were see through. Garments tended to go grey and start to fall apart when they had been worn and washed. A few children found that the garments made their skin more comfortable and helped them sleep better. They were disappointed that the miracle cure they hoped for did not happen. It is important and possible to involve children in studies like this so we can understand what they think about possible treatments for eczema.